Giant enhancement in Goos-Hänchen shift at the singular phase of a nanophotonic cavity - Sreekanth, Kandammathe Valiyaveedu (2019)
In this letter, we experimentally demonstrate thirtyfold enhancement in Goos-Hänchen shift at the Brewster angle of a nanophotonic cavity that operates at the wavelength of 632.8 nm. In particular, the point-of-darkness and the singular phase are achieved using a four-layered metal-dielectric-dielectric-metal asymmetric Fabry-Perot cavity. A highly absorbing ultra-thin layer of germanium in the stack gives rise to the singular phase and the enhanced Goos-Hänchen shift at the point-of-darkness. The obtained giant Goos-Hänchen shift in the lithography-free nanophotonic cavity could enable many intriguing applications including cost-effective label-free biosensors.